2004
DOI: 10.1074/jbc.m309333200
|View full text |Cite
|
Sign up to set email alerts
|

p16 Is Required for hSNF5 Chromatin Remodeler-induced Cellular Senescence in Malignant Rhabdoid Tumor Cells

Abstract: The hSNF5 chromatin-remodeling factor is a tumor suppressor that is inactivated in malignant rhabdoid tumors (MRTs). A number of studies have shown that hSNF5 re-expression blocks MRT cell proliferation. However, the pathway through which hSNF5 acts remains unknown. To address this question, we generated MRT-derived cell lines in which restoration of hSNF5 expression leads to an accumulation in G 0 /G 1 , induces cellular senescence and increased apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 56 publications
6
148
0
4
Order By: Relevance
“…Notably, different from what was reported for MRT cell models, restoration of SMARCB1 in VAESBJ expression failed to result in premature senescence. In MRTs cells, such a response relied on p16 activation (20). The fact that VAESBJ cells carry homozygous deletion of CDKN2A/p16 locus may account for the attenuation of the senescent phenotype in this cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, different from what was reported for MRT cell models, restoration of SMARCB1 in VAESBJ expression failed to result in premature senescence. In MRTs cells, such a response relied on p16 activation (20). The fact that VAESBJ cells carry homozygous deletion of CDKN2A/p16 locus may account for the attenuation of the senescent phenotype in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that VAESBJ represents a unique model to investigate the role of SMARCB1 inactivation in the context of epithelioid sarcoma. Because in MRTs cells, SMARCB1 tumor suppressor activity has been shown to impinge on cell proliferation (29,30), apoptosis (31), senescence (20,27), and cell motility (21), we investigated these phenotypes in SMARCB1-deleted VAESBJ epithelioid sarcoma cell line. Here, we provide evidence that SMARCB1 restoration in this cell line affects cell proliferation, enhances the sensitivity to genotoxic stress, and reduces cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the generation of a lentiviral expression vector for Mdm4, HA-Mdm4 (de Graaf et al, 2003) was cloned into pLV-CMVbc-GFP (Oruetxebarria et al, 2004) Table 1 for sequences). Subsequently, fragments containing the H1-promoter and cloned nucleotides were recloned into the PstI site of the lentiviral pRRL-CMV-GFP vector (Carlotti et al, 2004).…”
Section: Plasmids and Lentiviral Infectionsmentioning
confidence: 99%
“…Chromatin immunoprecipitation experiments have demonstrated the presence of hSWI/SNF on the cyclin D promoter, where it repressed transcription . Chromatin immunoprecipitation also demonstrated that hSWI/SNF members occupy the p16 INK4a and p21 WAF1/CIP1 promoters in vivo, where their presence is correlated with increased transcription (Lee et al, 2002;Kadam and Emerson, 2003;Kang et al, 2004;Oruetxebarria et al, 2004;Chai et al, 2005). The hSWI/SNF complex also regulates a diverse group of other mammalian target genes.…”
Section: Discussionmentioning
confidence: 97%